2019
DOI: 10.1038/s41366-019-0484-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of food craving is a metabolically active process in the brain in obese men

Abstract: Objective Obesity is associated with impaired inhibitory control over food intake. We hypothesized that the neural circuitry underlying inhibition of food craving would be impaired in obesity. Here we assessed whether obese men show altered brain responses during attempted cognitive inhibition of craving when exposed to food cues. Methods Sixteen obese men (32 ± 8.7 years old, BMI = 38.6 ± 7.2) were compared with 11 age-matched non-obese men (BMI 24.2 ± 2.5) using PET and FDG. Brain glucose metabolism was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Neuroimaging studies have reported brain activation in regions associated with reward and cogntive control in response to food cues in obese patients compared with controls (Volkow et al 2008;Garcia-Garcia et al 2013). Implicated regions include the prefrontal cortex (PFC), particularly the dorsolateral PFC (DLPFC) (Hare et al 2009;Lavagnino et al 2016), anterior cingulate cortex (ACC) (Rosenbaum et al 2008;Wang, Kojori, et al 2019a), and mesolimbic regions (Hare et al 2009;Lavagnino et al 2016). The PFC is crucial for executive function and cognitive control (Hare et al 2009;Hu et al 2016;Lavagnino et al 2016) and the DLPFC recruits inhibitory control to modulate eating behavior in response to tempting food (Batterink et al 2010;Lopez et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies have reported brain activation in regions associated with reward and cogntive control in response to food cues in obese patients compared with controls (Volkow et al 2008;Garcia-Garcia et al 2013). Implicated regions include the prefrontal cortex (PFC), particularly the dorsolateral PFC (DLPFC) (Hare et al 2009;Lavagnino et al 2016), anterior cingulate cortex (ACC) (Rosenbaum et al 2008;Wang, Kojori, et al 2019a), and mesolimbic regions (Hare et al 2009;Lavagnino et al 2016). The PFC is crucial for executive function and cognitive control (Hare et al 2009;Hu et al 2016;Lavagnino et al 2016) and the DLPFC recruits inhibitory control to modulate eating behavior in response to tempting food (Batterink et al 2010;Lopez et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous recording of the EGG in normal-weighted subjects at rest with the recording of brain activity with functional magnetic resonance imaging revealed regions where spontaneous fluctuations in the blood-oxygen-level-dependent signals were synchronized with the EGG rhythm. These regions include mid-cingulate areas, primary and secondary somatosensory cortices, and portions of the occipital lobe where food cravings could be modulated ( Rebollo et al, 2018 ; Wang G-J. et al, 2020 ; Wolpert et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These neural circuits are notable for being involved in emotional processing (54). Individuals with obesity may require greater effort to inhibit craving of pleasant but unhealthy foods (e.g., high calorie or high fat foods), especially in an emotional context (55).…”
Section: Discussionmentioning
confidence: 99%